Investigation On Antiproliferative Mechanisms Of Alstonia Angustilobasilver Nanoparticles In Skin Squamous Cell Carcinoma - Ab Rahim, Nurhidayah (2023)
Traditional methods of nanoparticles synthesis frequently use toxics chemicals and substantial energy, which may have detrimental effects on the environment and human health. Recently, plant-based synthesis of nanoparticles (AgNPs) has emerged as a promising green synthesis method. Herein, we reported the green synthesis of AgNPs using the aqueous extract of A. angustiloba leaves and assessed its antiproliferative mechanisms. Initially, the physiochemical properties of A. angustiloba-AgNPs were characterised using UV–Vis spectrophotometry, FT-IR, FESEM, EDX, TEM, XRD and zeta sizer analyses. The cytotoxicity of A. angustiloba-AgNPs was examined by MTT assays against the A431 cancer cell line. The morphology of the treated cells was examined using fluorescence microscopy and the antiproliferative mechanisms of the nanoparticles in A431 cells were investigated by annexin-FITC/propidium iodide (PI) staining and DNA cell cycle analysis using flow cytometry. The intracellular ROS levels were measured using a commercially available kit. The expression of apoptosis and cell cycle-related proteins was determined by Western blotting.